1986
DOI: 10.1002/tcm.1770060102
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in mutagenicity testing: I. Micronucleus and SCE tests in rats, mice, and Chinese hamsters with aflatoxin B1

Abstract: Three animal species used in in vivo mutagenicity testing--rats, mice and Chinese hamsters--were compared with respect to their mutagenic response to the mycotoxin aflatoxin B1 (AFB1). The micronucleus test and the SCE test with bone marrow cells were chosen as test methods, employing similar protocols for all species. The mutagenic potential of AFB1 was detected with rats and mice but not with Chinese hamsters. Rats were more susceptible to the mutagenic action of AFB1 than mice with regard to the effective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…It is a cofactor of the enzyme glutathione peroxidase (Leopold, 1976). Again, glutathione conjugates with AFB 1 (Madle et al, 1986). Thus, it could be possible that AFB 1 -induced oxidative damage acted as an intermediate for the genetic damage observed.…”
Section: Discussionmentioning
confidence: 97%
“…It is a cofactor of the enzyme glutathione peroxidase (Leopold, 1976). Again, glutathione conjugates with AFB 1 (Madle et al, 1986). Thus, it could be possible that AFB 1 -induced oxidative damage acted as an intermediate for the genetic damage observed.…”
Section: Discussionmentioning
confidence: 97%
“…474 recommends to use 5 animals per group and both sexes (OECD, 1997), but this study was performed only with male rats. Madle et al observed that AFB1 induced more MN in male rats and mice than in females (Madle et al, 2005) and it is very well known that OTA is more carcinogenic in male rodents than in females (Castegnaro et al, 1998;EFSA, 2006). Therefore, in order to simplify the design of the study which was technically complicated, it was decided to perform the study only in male rats.…”
Section: Discussionmentioning
confidence: 99%
“…The acute toxicity of cyclophosphamide is primarily associated with its genotoxicity Hayashi, 2000). In somatic cells, it provokes gene mutations, chromosomal aberrations, micronuclei and exchanges of sister chromatids in a variety of cell cultures with and without the presence of metabolic activation (Monteith, Vanstone, 1995;Elhajouji et al, 1994;Madle et al, 1986). Cyclophosphamide also damages chromosomes and micronuclei in the hematopoietic system of rats, mice and Chinese hamsters by producing highly reactive carbon ions (Moore et al, 1995).…”
Section: Discussionmentioning
confidence: 99%